2018
DOI: 10.1038/s41477-018-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Fern genomes elucidate land plant evolution and cyanobacterial symbioses

Abstract: Ferns are the closest sister group to all seed plants, yet little is known about their genomes other than that they are generally colossal. Here, we report on the genomes of Azolla filiculoides and Salvinia cucullata (Salviniales) and present evidence for episodic whole-genome duplication in ferns-one at the base of 'core leptosporangiates' and one specific to Azolla. One fern-specific gene that we identified, recently shown to confer high insect resistance, seems to have been derived from bacteria through hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
424
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 384 publications
(486 citation statements)
references
References 127 publications
23
424
0
2
Order By: Relevance
“…This could provide a safety net for possible random mutations in the PPR transcripts or in the target mRNA. Despite the high correlation of editing and ‘no phenotype’ seen in our analysis, it is worth pointing out that editing can play a crucial role in plants, especially in ferns where it has been reported that editing for the creation of the start codon is conserved and poses a selective advantage over having a translatable sequence encoded in the genome (Li et al ).…”
Section: Editing Is the Most Prevalent Function Of A Thaliana Ppr Prmentioning
confidence: 62%
“…This could provide a safety net for possible random mutations in the PPR transcripts or in the target mRNA. Despite the high correlation of editing and ‘no phenotype’ seen in our analysis, it is worth pointing out that editing can play a crucial role in plants, especially in ferns where it has been reported that editing for the creation of the start codon is conserved and poses a selective advantage over having a translatable sequence encoded in the genome (Li et al ).…”
Section: Editing Is the Most Prevalent Function Of A Thaliana Ppr Prmentioning
confidence: 62%
“…However, the phylogeny used for their dating analysis included only one fern species (the giant horsetail), with all other taxa being angiosperms; such a sparse sampling of ferns might have limited the power to estimate the age of the event. Li et al () recently reported the first two genome sequence datasets in ferns ( Salvinia and Azolla sps. of water ferns, Salviniaceae) and their detection of signals for an ancient WGD event from pairs of syntenic paralogs in the Salvinia genome as a peak in Ks distribution at ~1.2–1.3 (Li et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Li et al . () did find an HGT gene derived from cyanobacteria, but one that is shared with many other fern and lycophyte species (i.e. a more ancient HGT).…”
Section: The Role Of Hgt In the Evolution Of Fernsmentioning
confidence: 95%
“…Because of the species’ intimate association, they were identified as probable candidates for HGT. Surprisingly, no gene was found to be horizontally transferred between Azolla and the cyanobiont (Li et al ., ). Nevertheless, Li et al .…”
Section: The Role Of Hgt In the Evolution Of Fernsmentioning
confidence: 97%